Preparation and Characterization of a Novel Swellable and Floating Gastroretentive Drug Delivery System (sfGRDDS) for Enhanced Oral Bioavailability of Nilotinib - Hong-Liang Lin; Ling-Chun Chen; Wen-Ting Cheng; Wei-Jie Cheng; Hsiu-O Ho; Ming-Thau Sheu (MDPI AG, 2020)
Regarding compliance and minimization of side effects of nilotinib therapy, there is a medical need to have a gastroretentive drug delivery system (GRDDS) to enhance the oral bioavailability that is able to administer an optimal dose in a quaque die (QD) or daily manner. In this study, the influence on a swelling and floating (sf) GRDDS composed of a polymeric excipient (HPMC 90SH 100K, HEC 250HHX, or PEO 7000K) and Kollidon® SR was examined. Results demonstrated that PEO 7000K/Kollidon SR (P/K) at a 7/3 ratio was determined to be a basic GRDDS formulation with optimal swelling and floating abilities. MCC PH102 or HPCsssl,SFP was further added at a 50% content to this basic formulation to increase the tablet hardness and release all of the drug within 24 h. Also, the caplet form and capsule form containing the same formulation demonstrated higher hardness for the former and enhanced floating ability for the latter. A pharmacokinetic study on rabbits with pH values in stomach and intestine similar to human confirmed that the enhanced oral bioavailability ranged from 2.65−8.39-fold with respect to Tasigna, a commercially available form of nilotinib. In conclusion, the multiple of enhancement of the oral bioavailability of nilotinib with sfGRDDS could offer a pharmacokinetic profile with therapeutic effectiveness for the QD administration of a reasonable dose of nilotinib, thereby increasing compliance and minimizing side effects.